Patient Reported Outcome Measures in cancer care: a hybrid effectiveness-Implementation trial to optimise Symptom control and health service Experience (PROMISE)–protocol for a randomised controlled trial of electronic self-reporting of symptoms versus usual care during and following treatment in patients with cancer - David Wyld; Afaf Girgis; Elizabeth Miller; Penelope M Webb; Gunter Hartel; Karen Martin; Rahul Ladwa; Melissa Eastgate; Suzanne O’Brien; Sabe Sabesan; Raymond J Chan; Amy Brown; et al. (BMJ Open)
Introduction Routine collection of patient-reported outcome measures (PROMs) has the potential to inform and improve cancer care. It is now feasible for patients to complete PROMs electronically (ePROMs) providing information about their current levels of symptoms, side effects of treatment and other concerns. PROM scores can be tracked over time allowing more timely identification of problems and more appropriate intervention. Studies have reported clear benefits in patient–clinician communication when PROMs are used and trials in the USA and France found patients randomised to complete regular ePROMs reported better health-related quality of life, had fewer unplanned hospital visits and, importantly, significantly better survival than those randomised to usual care. However, information about the effects on health outcomes and, particularly, the cost-effectiveness of incorporating this information into practice is limited.Methods and analysis PROMISE (Patient Reported Outcome Measures in cancer care: a hybrid effectiveness-Implementation trial to optimise Symptom control and health service Experience) is a multicentre, randomised hybrid effectiveness/implementation trial to evaluate the clinical and cost-effectiveness of using ePROMs in routine cancer care to improve patient outcomes. Participants (target sample=572; randomised 1:1 to intervention and control) are adults aged 18 years or older diagnosed with a solid cancer and starting treatment at one of the four study hospitals. The primary outcomes are unplanned hospital presentations and physical/functional well-being at 6 months. We hypothesise that, compared with usual care, patients randomised to use an ePROM tool will have fewer unplanned hospital presentations, report better health-related quality of life and greater satisfaction with their care and that the ePROM tool will be cost-effective. We will also assess implementation and process outcomes consistent with the RE-AIM (Reach Effectiveness Adoption Implementation Maintenance) Framework.Ethics and dissemination This trial has been approved by the Metro South Human Research Ethics Committee (HREC/2020/QMS/67441). Participants provide written informed consent, including consent for record linkage, prior to completing the baseline questionnaire. Study results will be disseminated via peer-reviewed journals and presentations at scientific conferences and clinical meetings.Trial registration number ACTRN12620001290987.